Breastfeeding experiences and perspectives among women with postnatal depression: A qualitative evidence synthesis. Issue 3 (May 2020) - Da Silva Tanganhito, Daniela; Bick, Debra; Chang, Yan-Shing
Abstract: Background: Studies show that postnatal depression affects around 10–16% of women globally. It is associated with earlier cessation of breast feeding, which can negatively impact infants' long-term development. Mechanisms underpinning associations between mental health and women's decision to commence and continue to breastfeed are complex and poorly understood. Aim: The aim of this review was to investigate breastfeeding experiences, perspectives, and support needs of women with postnatal depression. No previous reviews were identified which had addressed this aim. Method: A systematic search was conducted of six databases to identify relevant qualitative studies. Six included studies were critically appraised and synthesised using thematic synthesis. Findings: Five themes were identified: (1) desire to breastfeed and be a 'good mother', (2) struggles with breastfeeding, (3) mixed experiences of support from healthcare professionals, (4) importance of practical and social support, (5) support for mental health and breastfeeding. Most women with postnatal depression expressed strong intentions to breastfeed, although some perceived 'failure' to breastfeed triggered their mental health problems. Practical and non-judgemental support for their mental health needs and for successful breastfeeding from healthcare professionals, family and friends are needed. Conclusion: Most women with postnatal depression desired to breastfeed but experienced breastfeeding difficulties that could impact on their mental health. By offering women with postnatal depression tailored and timely support, healthcare professionals could help women minimize breastfeeding problems which could consequently impact on their mental well-being and ensure they and their infants have opportunity to benefit from the advantages that breastfeeding offers.